Avaliação terapêutica do pimecrolimo creme 1% no tratamento da dermatite seborréica da face de pacientes com HIV- Positivos - Moraes, Andrea Pinheiro de (2006)
Seborrheic dermatitis (SD) is a one of the most common dermatosis in HIV-positive patients affecting between 40 to 80% of AIDS patients and 20 to 40% of HIV-positive patients. To investigate efficacy and safety of pimecrolimus cream 1% in HIV-positive patients with facial SD a phase II study was done. First of all 4 HIV-infected patients (Group A) with mild/severe SD were treated twice-daily with pimecrolimus cream 1% for 7 days and after this 21 HIV-infected patients (Group B) with mild/severe SD were treated twice-daily with pimecrolimus cream 1% for 14 days. Thereafter, treatment was discontinued and patients followed up for 5 weeks. Skin involvement (erythema, scaling, burning, pruritus, infiltration/papulation, excoriation and lichenification) at baseline, Days 7, 14, 21, 35 and 49 was assessed using a 4-point clinical score and digital photographs. Marked improvement was seen in clinical parameters at Day 7, with >= 90% patients clear of symptoms at Day 14. Erythema and scaling relapsed at Day 35 in approximately 50% of patients, but all symptoms were milder than at baseline. All patients responded to therapy, despite their immunologic status. Pimecrolimus cream represents a new, attractive and effective therapeutic option for facial SD in HIV-patients.